If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -1(3 + b) = -1(2b + -9) 3b + (3 * -1 + b * -1) = -1(2b + -9) 3b + (-3 + -1b) = -1(2b + -9) Reorder the terms: -3 + 3b + -1b = -1(2b + -9) Combine like terms: 3b + -1b = 2b -3 + 2b = -1(2b + -9) Reorder the terms: -3 + 2b = -1(-9 + 2b) -3 + 2b = (-9 * -1 + 2b * -1) -3 + 2b = (9 + -2b) Solving -3 + 2b = 9 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. -3 + 2b + 2b = 9 + -2b + 2b Combine like terms: 2b + 2b = 4b -3 + 4b = 9 + -2b + 2b Combine like terms: -2b + 2b = 0 -3 + 4b = 9 + 0 -3 + 4b = 9 Add '3' to each side of the equation. -3 + 3 + 4b = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 4b = 9 + 3 4b = 9 + 3 Combine like terms: 9 + 3 = 12 4b = 12 Divide each side by '4'. b = 3 Simplifying b = 3
| 3x-4+x=10 | | 3x-26=19 | | rx+2ry+kx+2ky= | | 5/3•(5) | | 50+73+146+161+x=360 | | X+(x+5)=57 | | 4.2m-1=-26.2 | | 102+75+136+2x+92+x=720 | | y=ky+kx+x+5 | | f(x)=2x/^3 | | ln(x+2)-ln(x)=4 | | x^2+57x-630=0 | | -8/x=7 | | 36-11x=13+12x | | logx^83=3 | | 9x-4*20=5*20 | | 8/5y-7=49 | | (x+20)0.75=x | | f(x)=1/sen^2x | | 120+120+120+120+x=720 | | 23w+15-5+2w=5 | | 78+42+42+x=360 | | 39+7m=95 | | 0.2p+2.2+2.2p=4.36 | | 3x-10+3x-10+52=180 | | 7(3-4x)=-63 | | 1/2x(x-3)=27 | | 3x-10+3x-10=52 | | (9x-5)+(4x+29)=26 | | 15n-65=130 | | 3x-10y=-11 | | Ntimes-5=-155 |